Efforts of Madrasah Heads In Improving The Quality of Education - Muhammad Mizan Asrori; Ibrahim (Center for Studies in Advanced Science, 2025)
The quality of education is an institutional benchmark for the wider community, for this reason, a madrasa head must improve madrasah programs to improve the quality of education in the institution. The conclusions of the results of this study indicate that: (1) The quality of education comes from the words quality and education. Quality in Arabic is